Low-Voltage Electrical Installations : (IEC, 2006)
Part 7-701:The particular requirements of this part of IEC 60364 apply to the electrical installations in locations containing a fixed bath (bath tub) or shower and to the surrounding zones as described in this standard. This standard does not apply to emergency facilities, e.g. emergency showers used in industrial areas or laboratories